Patterns, Determinants, and Elasticity of Household Food Consumption in Indonesia (Period 2021-2022) - Aulia, Wifa Darma; Yuliana, Rita (Politeknik Statistika STIS, 2024)
Introduction/Main Objectives: The increase in strategic food commodity prices significantly contributed to inflation, with the food, beverage, and tobacco category reaching 3.59% in March 2022. This price hike reduced household purchasing power, affecting welfare. This research examines how rising food prices impact household food consumption patterns in Indonesia. Background Problems: This study explores the effects of rising food prices on household consumption patterns. It addresses two key questions: What are household food consumption patterns, and what factors influence them? What is the elasticity of food demand in Indonesia between March 2021 and March 2022? Novelty: The study’s novelty lies in calculating food demand elasticity using demand theory assumptions, ensuring reliable results—unlike many studies that overlook these assumptions. Research Methods: The study uses the Linear Approximated-Almost Ideal Demand System (LA-AIDS) model with the Seemingly Unrelated Regression (SUR) method. Findings/Results: The results show that rising food prices in March 2022 changed household food consumption patterns. Own-price elasticity was negative, indicating reduced demand. Cross-price elasticity varied, with some food groups showing negative and others positive effects. All food groups were classified as normal goods based on expenditure elasticity.